INFLUENCE OF TRICEPS OVERHEAD EXTENSION EXERCISE WITH THE PYRAMID SYSTEM METHOD ON THE INCREASED ARM POWER AND LONG PASS RESULTS OF WATER POLO SPORTS - Utami, Starlet Viersa (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
In the water polo sport, several techniques must be mastered, one of which is the passing technique. A water polo player must be able to throw, both at close range and long-distance. The purpose of this study was to determine the effect of triceps overhead extension training with the pyramid system method on the increase in arm power and the results of long pass water polo. The research method that I use to test the hypothesis in this study is an experimental method. In this study, the population and sample used were all female athletes of water polo in West Java with 12 athletes because these athletes were still active and the majority had understood the basic techniques of passing and long pass movements. The form of training to increase arm power and the results of long pass water polo is given by weight training triceps overhead extension with the pyramid system method. The treatment was given in 16 meetings to 12 West Java female water polo athletes. The data analysis technique used was the t-test at the 95% significance level. Based on the results of data processing, the researcher concluded that the exercise treatment had a significant effect on increasing arm power and the results of the long pass water polo from the initial test data obtained with an average of 386.08 and the final test data of 421.33 for arm power. while for the long pass data, the average of the initial test was 17.21 and the final test was 18.01.